2020
DOI: 10.1002/jdd.12190
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of individual and team readiness assurance tests in a modified team based learning method

Abstract: Objective Team based learning (TBL) is shown to have a positive impact on learning abilities. In this study, we compared the individual and group readiness assurance grades of dental students toward a modified TBL protocol for an orthodontic topic. Methods All of the dentistry students in 2 different annual intakes from Shiraz University of Medical Sciences took part in the study. The references and methods for holding the class was presented to the vice dean of educational affairs and to the students. At the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The results of this research corroborate previous studies that have demonstrated that TBL method is a promising way to teaching in dentistry course [43][44][45]. The complexity of subjects also showed to influence on the effectiveness of teaching-learning method and consequent students' performance.…”
Section: Discussionsupporting
confidence: 88%
“…The results of this research corroborate previous studies that have demonstrated that TBL method is a promising way to teaching in dentistry course [43][44][45]. The complexity of subjects also showed to influence on the effectiveness of teaching-learning method and consequent students' performance.…”
Section: Discussionsupporting
confidence: 88%
“…The behaviorist approaches with an emphasis on content transfer are not compatible with nowadays learning context and students prefer methods based on problem‐solving, critical thinking, and interpersonal interactions and communications (Blouin et al, 2009 ; Eachempati et al, 2016 ; Karandish, 2020 ). It should also be noted that students have different individual capabilities and learning styles, and traditional education cannot fulfill this variety of learning styles (Alcota et al, 2011 ; Smolen et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The behaviorist approaches with an emphasis on content transfer are not compatible with nowadays learning context and students prefer methods based on problem solving, critical thinking and interpersonal interactions and communications (11,4,12). It should also be noted that students have different individual capabilities and learning styles, and traditional education cannot ful ll these variety of learning styles (13,14).…”
Section: Introductionmentioning
confidence: 99%